1.Wynik każdego z działań zapisz w postaci potęgi:
a)2³*8³=
b)5⁻²*(-15)⁻²=
c)(-7)⁻¹*3⁻¹=
d)(⅙)²*13²=
e)(⅔)⁻⁶*(5/7)⁻⁶=
f)0,8⁸⁵*0,9⁸⁵=
g)2³:7³=
h)5⁻²:(-13)⁻²=
i)(-7)⁻¹:13⁻¹=
j)(13/6)²:13²=
k)(2/3)⁻⁶:(3/7)⁻⁶=
l)0,7⁶:0,9⁶=

2

Odpowiedzi

2009-10-24T15:57:12+02:00
A)2³*8³=2³*(2³)³=2³*2⁹=2¹²=4096
b)5⁻²*(-15)⁻²=(-75)⁻²=(-1/75)²=1/5625
c)(-7)⁻¹*3⁻¹=(-21)⁻¹=-1/21
d)(⅙)²*13²=(13/6)²=169/36=4 25/36
e)(⅔)⁻⁶*(5/7)⁻⁶=(10/21)⁻⁶=(21/10)⁶=85766121/1000000=85,766121
f)0,8⁸⁵*0,9⁸⁵=0,72⁸⁵≈7,47
g)2³:7³=(2/7)³=8/343
h)5⁻²:(-13)⁻²=(-5/13)⁻²=(-13/5)²=-169/25=-6,76
i)(-7)⁻¹:13⁻¹=(-7/13)⁻¹=-13/7
j)(13/6)²:13²=(⅙)²=1/36
k)(2/3)⁻⁶:(3/7)⁻⁶=(14/9)⁻⁶=(9/14)⁶=531441/7529536
l)0,7⁶:0,9⁶=(7/9)⁶=117649/531441
1 5 1
Najlepsza Odpowiedź!
2009-10-24T15:59:37+02:00
A)2³*8³= 16³
b)5⁻²*(-15)⁻²=-3⁻²
c)(-7)⁻¹*3⁻¹=-21⁻¹
d)(⅙)²*13²=⅙²*13/1₂=13/6²
e)(⅔)⁻⁶*(5/7)⁻⁶=10/21⁻⁶
f)0,8⁸⁵*0,9⁸⁵=0,72⁸⁵
g)2³:7³=0.28³albo 2/7³
h)5⁻²:(-13)⁻²=-0.38⁻² albo -5/13⁻²
i)(-7)⁻¹:13⁻¹=0.53⁻¹ albo -7/13⁻¹
j)(13/6)²:13²=13/6²÷13/1²=13/6²*1/13²(13 się skrócą)=6²
k)(2/3)⁻⁶:(3/7)⁻⁶=2/3⁻⁶×7/3⁻⁶=14/9⁻⁶
l)0,7⁶:0,9⁶= 0.63⁶ albo 7/9⁶